Construção da escala avaliativa do risco de quedas (EARQUE) para pessoas idosas não institucionalizadas - Jonas, Lucélia Terra (2013)
The global aging brings up the discussion regarding of incapacitating events, among them the occurrence of falls at domicile, which may compromise the health and life quality of the elderly. This study aimed to construct an evaluative scale of risk factors for falls in older people non-institutionalized. Therefore, was performed a study of methodological type, employing the theoretical procedures of Psychometry for construction of measure instruments. Thereby, was elaborated a minitheory about the construct "risk of falls", with the establishment of the falls definition of risk of falls, and operational definition of each risk factor, which guided the development of items in the construction of the instruments. Were identified 56 major risk factors for falls in older people, 32 biological, 13 behavioral, four socioeconomic and eight environmental factors related to the inside of the home. Such factors constituted the Evaluative Scale of the Risk of Falls (EARQUE), in turn organized in two sections, being section A with 32 items and B with 23, totaling 55 items. The EARQUE characterized as evaluative unpublished instruments destined to estimate the risk of falls in elderly non-institutionalized and may be converted at useful tools for application in clinical practice and, similarly, in research.